2020
DOI: 10.1111/ocr.12380
|View full text |Cite
|
Sign up to set email alerts
|

Sella turcica morphometrics in children with unilateral cleft lip and palate

Abstract: Objective: To use morphometric methods to investigate the size and shape of the sella turcica in children with unilateral cleft lip and palate (UCLP). Setting and sample population: Fifty-six healthy children with non-syndromic UCLP, from a major paediatric teaching hospital, with lateral cephalograms taken prior to alveolar bone grafting, were compared with an age-and sex-matched control group of healthy children without orofacial clefts, with lateral cephalograms taken prior to orthodontic treatment. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…When sella turcica was examined in subjects with other pathological conditions either syndromic (e.g., Williams syndrome) or with multifactorial etiology (e.g., cleft lip and palate) significant dimensional differences were evident Antonarakis et al, 2020). On 55 the contrary to the present study, sella turcica in the aformentioned conditions presented decreased sized in comparison with healthy controls Antonarakis et al, 2020).…”
Section: Sella Sizecontrasting
confidence: 87%
See 2 more Smart Citations
“…When sella turcica was examined in subjects with other pathological conditions either syndromic (e.g., Williams syndrome) or with multifactorial etiology (e.g., cleft lip and palate) significant dimensional differences were evident Antonarakis et al, 2020). On 55 the contrary to the present study, sella turcica in the aformentioned conditions presented decreased sized in comparison with healthy controls Antonarakis et al, 2020).…”
Section: Sella Sizecontrasting
confidence: 87%
“…Finally, it is interesting that the results related to the principal components (PCs) present differences from the studies on sella shape of Antonarakis et al and Andreadaki et al on unilateral cleft lip and palate subjects and non-cleft and non-syndromic individuals respectively (Andredaki et al, 2007;Antonarakis et al, 2020). In the first study conducted by Antonarakis et al the variance of PC1, PC2 and PC3 were 57,8 %, 26,9%, and 8,6% respectively, whereas Andreadaki et al presented similar values (Andredaki et al, 2007;Antonarakis et al, 2020). Interestingly in the present study the first three PC presented more evenly distributed variance.…”
Section: Sella Shapementioning
confidence: 97%
See 1 more Smart Citation
“…Thus, it can be inferred that the sphenoid is a controversial and significant structure regarding not only the morphogenesis of the cranial base but also the features of a human-specific cranium and face. Furthermore, it has been reported that malformations of the sphenoidal region can be observed in many congenital craniofacial deformities, including craniosynostosis, cleft lip and palate 12 , 13 , Down syndrome 14 16 , and others 17 , 18 , which emphasize the importance of the sphenoid in the pathogenesis of these anomalies. Recent advances in imaging techniques have led to the realization of the significance of the sphenoid, including evolutionary and developmental aspects, and many anatomists have been keenly interested in the unique shape of the sphenoid as it has been called by various names since ancient Greece 19 ; however, the detailed process of the morphogenesis of the sphenoid itself remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…13 According to the previous studies, the sella turcica is smaller in all dimensions in patients with unilateral lip/palate cleft compared to the individuals without cleft. 14 Moreover, the prevalence of STB and PP in patients with cleft is relatively high. 10,15 The previous studies have measured the presence of PP and STB among western and Asian populations 1616 but through the review of literature, we have found that the prevalence of these measures and their association with cleft lip/palate have not yet been studied in the Iranian population.…”
Section: Introductionmentioning
confidence: 99%